Die Staatsunabhängigkeit der Medien Analyse eines verfassungsrechtlichen Prinzips im Spannungsverhältnis zur Staatsverantwortung im Medienbereich und zur staatlichen Öffentlichkeitsarbeit unter Berücksichtigung des digitalen Wandels - Piolino, Marina (sui generis Verlag, 2022)
If the journalistic media are to be able to effectively perform their essential democratic tasks of forming public opinion and controlling state power, they must be independent of the state. At the same time, this state has to guarantee a diverse range of media and to inform the public about its activities. This tension is intensifying in the internet age, in which the expensive production of journalistic content is less and less taken for granted. This updates the state's duty to ensure media pluralism, for example by organizing a public service system or other promotional measures, and to carry out active public relations work. This in turn increases the risk that the state will influence media activity or become the media provider itself. The limits that the state has to observe in this context are worked out in this book on the basis of a cross-media, constitutional and international law analysis of the principle of the media's independence from the state.